2015
DOI: 10.1371/journal.pone.0123395
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption of Trivalent Arsenic from Water by Functionalized Diatom Silica Shells

Abstract: The potential of porous diatom silica shells as a naturally abundant low-cost sorbent for the removal of arsenic in aqueous solutions was investigated in a batch study. The objective of this work was to chemically modify the silica shells of a diatom Melosira sp. with bifunctional (thiol and amino) groups to effectively remove arsenic in its toxic As(III) form (arsenite) predominant in the aquatic environment. Sorption experiments with this novel sorbent were conducted under varying conditions of pH, time, dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…The mostly available forms of As in water are the inorganic species arsenate [As(V)] and arsenite [As(III)]. The As(V) species occurs as oxyanions (H 2 AsO 4 − and HAsO 4 2− ) at neutral pH, while the arsenic(III) species is neutral H 3 AsO 3 [1][2][3]. As(III) is more toxic and more difficult to remove by physico-chemical treatment than As(V) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The mostly available forms of As in water are the inorganic species arsenate [As(V)] and arsenite [As(III)]. The As(V) species occurs as oxyanions (H 2 AsO 4 − and HAsO 4 2− ) at neutral pH, while the arsenic(III) species is neutral H 3 AsO 3 [1][2][3]. As(III) is more toxic and more difficult to remove by physico-chemical treatment than As(V) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bioflocculants such as diatom silica shells and Arthrobacter spp. biomass are applicable in removing heavy metals, including arsenate, from wastewater [ 6 , 7 ]. Bioflocculation is considered an active process caused by living cells due to the production of exopolymeric macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thermodynamically decreased randomness at the solid–solution interface was indicated by the negative value of normalΔ S (−92.20 ± 1.42 kJ mol −1 K −1 ) and the adsorption process was found to be exothermic in nature due to normalΔ H values (−35.31 ± 0.44 kJ mol −1 ). Collectively, all of these results suggested that the mechanism mainly responsible for the adsorption is chemisorption . The thermodynamics data of As using copper(II) oxide nanoparticles suggested that the process was feasible, spontaneous and endothermic in nature with normalΔ H = 120.78 kJ mol −1 which falls in the physicochemical adsorption process range .…”
Section: Biosorption Kinetics and Thermodynamicsmentioning
confidence: 92%
“…The Sips model can be expressed as shown in Eq. : qnormale=qnormalmtrue(KLFCnormaletrue)inormalbtrue[1+true(KLFCnormaletrue)inormalbtrue] where q m is the monolayer adsorption capacity of the sorbent (mg g −1 ), K LF (L mg −1 ) 1/b is the Langmuir–Freundlich constant, and b (dimensionless) is the Langmuir–Freundlich heterogeneity constant . For adsorption of As(III) on modified diatom silica shells, this model was found to fit best with the experimental data ( R 2 = 0.94–0.99).…”
Section: Biosorption Isothermsmentioning
confidence: 94%